PHENOTYPES OF COPD PATIENTS WITH RESPIRATORY FAILURE AND THEIR RESULTS IN ICU SETUP: A CROSS-SECTIONAL OBSERVATIONAL STUDY. - Ranjan, Rajeev; Singh, Utkarsh; Singh, Devendra Prasad (Student’s Journal of Health Research Africa, 2024)
Background Airflow restriction and persistent respiratory symptoms are characteristic features of Chronic Obstructive Pulmonary Disease (COPD). The intricacy of the disease is shown by the phenotypic diversity of individuals with COPD who are experiencing respiratory failure in the Intensive Care Unit (ICU). The study aimed to investigate the phenotypes of COPD patients with respiratory failure and analyze their outcomes over one year. Methods A study was carried out enrolling 80 COPD patients admitted to the ICU due to respiratory failure. Patients aged 40 years and above with confirmed COPD diagnosis were included. Data on demographics, COPD severity, exacerbation history, comorbidities, and ICU admission details were collected. Pulmonary function tests, arterial blood gas analysis, and information on respiratory support modalities were documented. Phenotypic characterization was performed using established criteria, and outcome measures included mortality rates and ICU stay duration. Results The study population was 65% male and averaged 65 years old. Patients were 40% emphysema-dominant, 30% chronic bronchitis-dominant, and 30% mixed. Emphysema-dominant patients had worse airflow limitation. Hypertension, coronary heart disease, and diabetes were frequent. Hypoxemia and hypercapnia were seen in pulmonary function tests. Mechanical breathing was needed by 70% of patients, and ICU mortality was 25%. In long-term survival studies, exacerbation frequency, and comorbidities significantly predicted a 40% one-year mortality rate. Conclusion The study highlights the diverse phenotypes of COPD patients with respiratory failure and their associated outcomes. Personalized management strategies tailored to specific phenotypes and addressing comorbidities are crucial for improving patient outcomes. Further research is needed to refine treatment approaches and enhance long-term survival in this population. Recommendations Clinicians should consider phenotypic variations and comorbidities when managing COPD patients with respiratory failure. Interventions targeting exacerbation prevention and comorbidity management may improve outcomes. Future studies should focus on elucidating the underlying mechanisms driving phenotypic differences and developing targeted therapies.